MOG associated autoimmune encephalomyelitis with active disease dynamic in imaging examinations and minimal clinical manifestation - Tilindytė , E.; Muliuolis , I.; Samaitienė , R. (Neurologijos seminarai, 2019)
Anti-MOG-associated encephalomyelitis is an inflammatory demyelinating disease in which auto-antibodies against myelin oligodendrocyte glycoprotein (MOG) are detected in the patient’s serum. MOG spectrum disorders include the following pathologies: optic neuritis, myelitis, brain or brainstem encephalitis, and acute disseminated encephalomyelitis. Most often, the disease first manifests as acute disseminated encephalomyelitis, less often as optic neuritis. Progressive encephalopathy and multiple focal neurological symptoms are characteristic to this disease: irritability, disturbed consciousness, weakness, sensory disorders, bowel, bladder dysfunction, spasticity, hyperreflexia, positive Babinsky reflex, paresis, cerebral ataxia, cerebral neuropathy, and spinal cord dysfunction (transverse myelitis). Glucocorticoids are used for treatment and a fast response is observed in most cases. If the disease is relapsing, intravenous immunoglobulin, azathioprine, mofetil mycophenolate, and rituximab are recommended. This case report describes a 6-year-old patient with MOG spectrum multiphase disseminated encephalomyelitis. The onset of the disease was subacute: firstly, the girl became sleepy during daytime and for a month she had a gradually increasing leg pain when standing, therefore she stopped walking. After a few more days, the girl presented with urinary retention and was admitted to the hospital. The diagnosis was confirmed by magnetic resonance imaging (MRI) of the head and neck as well as by serum MOG antibody testing. Treatment with methylprednisolone pulse therapy and prednisolone resulted in the disappearance of clinical symptoms within a few weeks. However, this treatment was not effective enough – although regression of the brain lesions was observed in the MRI, new lesions were not prevented. Relapse of the disease was observed on the repeated MRI, but no clinical symptoms appeared. For the treatment of relapse, a monthly intravenous immunoglobulin course was given 5 times in total. Treatment with intravenous immunoglobulin was more effective due to regression of the lesions and a longer disease remission. However, eventually the disease relapsed again presenting with clinical symptoms and MRI lesions, suggesting that the treatment duration was not long enough.